Test scores and economic growth: Update and extension - Gabriel Heller-Sahlgren; Henrik Jordahl (Research Institute of Industrial Economics (IFN), 2021)
Research indicates that education quality - measured by test scores in international student surveys - predicts economic growth. In this paper, we extend previous findings up to 2016 and analyse test scores of upper-secondary school students only. We find that the positive relationship between growth and test scores holds in both cases. The share of top-performing students exhibits a stronger correlation with economic growth than does the share of students who meet basic requirements.
Keywords: I25; O15; O57; 330; Education; Economic growth; PISA; TIMSS; Top-performing students